Designing a rubric to assess student engineering projects - Shafie, Amir Akramin (IIUM Press, 2009)
In order to bridge the gap between a student understanding and an instructor's perception of subject mastery, it is important to assess upper year capstone engineering project in a way which targets the important aspects within each stage in the design process while providing feedback that is instructive and helpful. Using the engineering development process itself, a rubric was created to assess a student mastery of the engineering development process of an engineering project. The rubric assesses student five general areas, Fundamental (F), Analysis (A), Design (D), Ethics, Safety, Society and Environment (ESSE) and Work skill (WS). These areas fully encompass the goals of the engineering development phase, not only in terms of the project's completion, but also relate to the learning goals that instructors should have for the student, as well as providing feedback that can help develop a student's mastery of the topic area.